Reeds VHF-DSC handbook - Fletcher, Sue (Adlard Coles Nautical Press, 2011)
The Reed's VHF DSC Handbook is a user-friendly guide that gets marine VHF radio users quickly up to speed with both the analogue and digital functions on the radio. Sue Fletcher's straightforward explanations and tips describe the leisure craft VHF DSC radio system in detail and its place within GMDSS. Since it was first published it has become the standard work on the subject. Updated to take into account new developments and procedures it provides: all the information required to pass the Short Range Certificate (SRC) - which is compulsory for anyone using a VHF DSC radio;radio procedure